Attitudes Towards Paying Taxes in Austria: An Empirical Analysis - Benno Torgler; Friedrich Schneider (Center for Research in Economics, Management and the Arts (CREMA), 2004)
People mostly pay their taxes although there is a low probability of getting caught and being penalized. Thus, new attempts in the tax compliance literature try to go beyond standard economic theory. This paper examines citizens' attitudes toward paying taxes - what is sometimes termed their "tax morale", or the intrinsic motivation to pay taxes. Tax morale may be a key determinant to explain why people are honest. However, there are very few papers that explore the concept of tax morale theoretically and empirically. This study, based on the World Values Survey and the European Values Survey, therefore attempts to fill this gap in the literature, focusing on tax morale in Austria. Societal institutions such as trust or pride have been identified as key determinants that shape tax morale in Austria. Furthermore, a lower perceived compliance leads to a decrease of tax morale, which indicates that social comparisons are relevant. The results also show a decrease of tax morale between 1990 and 1999, although Austria's taxpayers still have a very high tax morale compared to other European countries.
Keywords: H26; H73; D64; 330; Tax Morale; Societal Institutions; Austria